Spectacular Transformation to Spectacular Failure: Enron and the Us Regulatory Changes - ., . (International Journal of Engineering and Technology, 2018)
Enron was the blossoming company known around the world for its â€œspectacular transformation from domestic pipeline business to fully integrated global energy companyâ€ (Seitts, 2016). Americaâ€™s new shining star soon fell in the year of 2002. Enron was providing false information to stakeholders and investors making the company seem much more profitable than it truly was. The country had been fighting financial schemes since its creation. Laws were already put in place to deter fraud and prevent mass destruction in the stock market. These laws did not cover every aspect of the business world, so the government had to create a new act that would specifically lay out criteria for all layers of publicly traded companies. The Sarbanes-Oxley act was passed in 2002 and the act targeted not only internal decision makers but also external information holders such as auditors and banks. The SOX act was not perfect and did not solve all of the problems in the financial market but did lay out additional guidelines and penalties when it came to fraudulent misrepresentation.